Plazos de prescripción de las obligaciones patrimoniales surgidas del daño ambiental - Montero Bustabad, Daniel (2013)
The following article deals with an important issue for the legal practice before the Environmental Administrative Court’s (Tribunal Ambiental Administrativo): prescription terms concerning: 1. Protective environmental injunctions. 2. Several elements that conform damages’ responsibility issuing from environmental torts. Unlike what many Attorneys assume, as a general rule, there are no prescription terms issuing from pure ecological torts... until they are restored in their fullest extent. The few causes of prescription are limited to “private” (non-pure) torts or, concerning pure ecological torts, for those elements in damages’ responsibility that are limited to torts against the society as a whole, not against natural elements as such.